Correlation Between Striatal Dopamine D2/D3 Receptor Binding and Cardiovascular Activity in Healthy Subjects - Yeh, Tzung-Lieh; Yang, Yen-Kuang; Chiu, Nan-Tsing; Yao, Wei-Jen; Yeh, Shoou-Jeng; Wu, Jin-Shang; Chuang, Jih-Ing; Chang, Shei-Hsi (American journal of hypertension, 2006)
Background: The relationship between the striatal dopaminergic system and cardiovascular activity is not well known. The aim of this study is to investigate the relationship between striatal D2/D3 receptor binding and cardiovascular activity. Methods: The striatal D2/D3 receptor binding of 34 healthy volunteers was assessed by the single-photon emission computed tomography (SPECT) imaging method with the [123I]-iodobenzoamide (IBZM) ligand. The ratio of the radioactivity in the striatum (St) and the frontal cortex (Fc) (St/Fc ratio) was used as the marker for striatal D2/D3 receptor binding. Their cardiac autonomic functions were measured by continuously monitoring their heart rate and blood pressure (BP) in supine position during 10 min. The heart rate variability (HRV) was analyzed by spectral analysis and the geometric method. Results: The St/Fc ratio of striatal dopamine D2/D3 receptor binding correlated negatively with heart rate (HR), and positively with cardiac vagal index (CVI) and low frequency (LF) power in healthy subjects who were in a supine resting position. Conclusions: Striatal dopamine D2/D3 receptors may play a part in cardiovascular regulation.